Toward enhanced competence acquisition in clinical practice: implementing blended learning for physical therapy students - Bermejo-Franco, Alberto; García-Arrabé, María; Díaz-Meco-Conde, Raquel; González-Fernández, Laura; Ruiz-Ruiz, Beatriz; del Prado-Álvarez, Rebeca; Aladro-Gonzalvo, Arian Ramón (Frontiers in Education, 2024)
Background The curricular changes in educational activities, teaching methodologies, and assessment systems brought about by the COVID-19 closure, which restricted attendance in curricular practices, required adjustments. However, the impact of these curricular adaptations on the acquisition of competencies in the clinical context has not been sufficiently explored. Objective The objective of this study was to assess the potential impact on the expected learning outcomes in the Basic Manual Therapy course following curricular adaptations made during the COVID-19 lockdown. We specifically must be focused on acquiring competencies related to the clinical domain, including clinical practice, medical history, and reflective journaling during clinical practices. We aimed to compare these experiences with those of students who did not undergo any adaptations in the previous academic year. Methods This is a retrospective cohort study in a sample of physical therapy university students, conducted in accordance with Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines. We divided students into two groups based on when they enrolled: the ‘non-exposed group’ (NE), which includes those who finished the Basic Manual Therapy course in 2018–2019 and Clinical Stays I in 2019–2020, and the ‘exposed group’ (E), consisting of students who completed the Basic Manual Therapy course in 2019–2020 and later took part in Clinical Stays I during 2020–2021. Results A total of 282 students were included in the study. The results indicated that the curricular adaptations implemented for the Basic Manual Therapy [U(E Mdn = 7.7000, NE Mdn = 7.7000) = 9,286, z = −0.546, p = 0.585] and Clinical Stays I subjects [U(E Mdn = 8.5900, NE Mdn = 8.4700) = 9,600, z = −0.078, p = 0.938] did not have a statistically significant impact on the acquisition of competencies and learning outcomes when comparing the two groups. Most differences between groups were observed in reflective journaling marks [U(E Mdn =8.300, NE Mdn = 8.000) = 7770.5, z = −2.796, p = 0.005] and Student Progress item of this Reflective Journaling [U(E Mdn = 9.000, NE Mdn = 8.000) = 7216.5, z = −3,668, p = 0.000], favoring the E cohort. In both groups, a low and positive correlation was found between the ordinary BMT mark and the ordinary CS I mark [Rho (E = 0.206, NE = 0.170), p < 0.05]. Conclusion While this study has certain limitations, the findings highlight that the non-face-to-face curricular adjustments implemented during the COVID-19 pandemic, as a substitute for in-person teaching, effectively prevented the pandemic from negatively impacting the acquisition of clinical skills. The activities designed in Basic Manual Therapy subject facilitated positive skill development in Clinical Practice for students in clinical physiotherapy stays, contributing to good learning outcomes, especially in the formulation of Clinical History and Reflective Journaling.